Layanan Bimbingan Belajar sebagai Upaya Peningkatan Kualitas Proses Belajar Mengajar - Zaenal Abidin (Fakultas Tarbiyah dan Ilmu Keguruan IAIN Purwokerto, 2015)
According to the real result of the various studying difficulties,which being felt by the client (student), whatever their reasons or motives are very much demand to the guider to take part in looking for the various alternatives in order to help the studentresolving those cases through the learning guidance services actively. This activity is in order to create the student’s mental stability and their readiness to promote their aptitude and full participation, especially in learning process (in theclass). If this condition can be realized be expected to obtain the quality of learning-teaching process in the class.